The role of rosette formation in pathogenesis of vivax malaria / Lee Wenn Chyau - Lee, Wenn Chyau (2014)

(untitled)
Rosette formation is one of the unique biological phenomena that have been linked to pathobiology of malaria. It is believe to be associated with the severe outcomes of falciparum malaria. Most of the knowledge about rosetting is obtained from in-depth studies conducted on Plasmodium falciparum. However, the rosetting phenomenon and pathobiology of vivax malaria is not well studied. This research project aimed at deciphering the unknown aspects behind rosetting phenomenon of P. vivax, and investigating the role of rosette formation in pathobiology of vivax malaria. In total, 121 fresh P. vivax isolates, 48 cryopreserved P. vivax isolates, 122 fresh P. falciparum isolates and 5 cryopreserved P. falciparum isolates were recruited into this research project. A novel technique suitable for reticulocyte characterization and rosetting assay in field setting was developed from this research project. Based on the field studies conducted, rosette formation is common in P. vivax. However, rosetting is not significantly correlated to clinical parameters such as reticulocyte count and parasitaemia. Besides, cryopreservation and thawing processes affect the rosetting capability of P. vivax isolates. Rosette formation was found to be initiated at the early trophozoite stage of P. vivax and the rosetting development reached plateau at the end of the erythrocytic maturation. Giant rosettes were found more frequently in P. vivax than P. falciparum. In addition, gametocytes were found to be involved in rosette formation. Unlike P. falciparum, the rosetting phenomenon of P. vivax is independent of human ABO blood groups and complement receptor 1 (CR1/CD35). However, rosetting phenomena of P. vivax and P. falciparum are dependent on the BRIC4 region of human glycophorin C (CD236R), strongly indicating the BRIC4 region of CD236R as another rosetting coreceptor for P. vivax and P. falciparum. On elucidating the roles of rosette formation in pathobiology of malaria, the significantly high preference for normocytes instead of reticulocytes in rosette formation clearly shows that rosetting is iii unlikely to assist merozoite reinvasion in vivax malaria. Furthermore, increased rosetting rates upon exposure to anti-malaria drug compounds and human white blood cells suggest that the rosetting phenomenon may serve as an intrinsic protective mechanism of the malaria parasites against their environmental threats.